1997
DOI: 10.1074/jbc.272.20.12989
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization and Sequestration of Human m2 Muscarinic Acetylcholine Receptors by Autoantibodies from Patients with Chagas' Disease

Abstract: Chronic Chagas' disease is associated with pathologic changes of the cardiovascular, digestive, and autonomic nervous system, culminating in autonomic denervation and congestive heart failure. Previously, circulating autoantibodies that activate signaling by cardiac muscarinic acetylcholine receptors (mAChRs) have been described. However, it remains unclear whether the chagasic IgGs directly interact with the m2 mAChRs (predominant cardiac subtype), and, if so, whether chronic exposure of the mAChRs to such ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 29 publications
0
20
0
4
Order By: Relevance
“…As mentioned earlier in the example of bias for the CaSR (Makita et al, 2007), autoantibodies can act allosterically to mediate pathophysiology. Other examples where this has been seen include Chagas disease, a parasitic infection by Trypanosoma cruzi that leads to the generation of allosteric antibodies targeting b 1 adrenergic and M 2 mAChRs in the heart (Leiros et al, 1997;Sterin-Borda et al, 1999;Hernandez et al, 2003), and Sjogren syndrome, an autoimmune disorder associated with dysfunction of secretory glands that has been proposed to be mediated, at least in part, by autoantibodies against various mAChR subtypes (Borda et al, 1996). Interestingly, the polycationic human eosinophil major basic protein (MBP), a peptide that constitutes ∼50% of the inflammatory peptides released after infiltration and degranulation of eosinophils (Verbout et al, 2007), has been shown to specifically bind to the M 2 mAChR, potentially in an allosteric fashion (Jacoby et al, 1993).…”
Section: Endogenous Allosteric Modulatorsmentioning
confidence: 99%
“…As mentioned earlier in the example of bias for the CaSR (Makita et al, 2007), autoantibodies can act allosterically to mediate pathophysiology. Other examples where this has been seen include Chagas disease, a parasitic infection by Trypanosoma cruzi that leads to the generation of allosteric antibodies targeting b 1 adrenergic and M 2 mAChRs in the heart (Leiros et al, 1997;Sterin-Borda et al, 1999;Hernandez et al, 2003), and Sjogren syndrome, an autoimmune disorder associated with dysfunction of secretory glands that has been proposed to be mediated, at least in part, by autoantibodies against various mAChR subtypes (Borda et al, 1996). Interestingly, the polycationic human eosinophil major basic protein (MBP), a peptide that constitutes ∼50% of the inflammatory peptides released after infiltration and degranulation of eosinophils (Verbout et al, 2007), has been shown to specifically bind to the M 2 mAChR, potentially in an allosteric fashion (Jacoby et al, 1993).…”
Section: Endogenous Allosteric Modulatorsmentioning
confidence: 99%
“…Posteriormente, se pueden encontrar múltiples focos inflamatorios en el sistema de conducción, nidos de parásitos dentro del nodo aurículo-ventricular, periganglionitis auricular importante y perineuritis (90). También se han encontrado anticuerpos circulantes contra receptores colinérgicos y adrenérgicos de linfocitos y de miocardio en los pacientes infectados por T. cruzi (91)(92)(93).…”
Section: Neurotripanosomiasis Autonómicaunclassified
“…En pacientes con enfermedad de Chagas con cardiopatía crónica y en fase indeterminada, se ha descrito la presencia de anticuerpos circulantes que reconocen los neurorreceptores b -adrenérgicos y colinérgicos muscarínicos cardíacos del tipo II (anti-m2MAChR) que tienen actividad funcional en modelos in vitro e in vivo (5)(6)(7)(8)(9)(10)(11).…”
unclassified
“…La reactividad de los anticuerpos anti-m2MAChR ha sido descrita contra el tercer dominio intracelular del receptor (12), pero la mayoría de estudios se han centrado en la reactividad dada por el reconocimiento de una secuencia de 25 aminoácidos correspondiente al segundo aro extracelular del m2-MAChR (6,8,11,13) (figura 1). En ensayos in vitro, se ha evaluado la capacidad funcional de este reconocimiento y se ha demostrado que el acople del receptor con los anticuerpos produce una respuesta fisiológica similar a la del ligando natural, dada por la disminución en la fuerza de contracción del tejido cardiaco (14), la variación en los niveles intracelulares de AMPc y GMPc (5,(8)(9)(10), la supresión de corrientes de calcio (15,16) y la pérdida de la sensibilización del receptor (11).…”
unclassified